Complex networks : an algorithmic perspective - Erciyes, Kayhan (CRC Press/Taylor & Francis, 2014)
"Network science is an emerging field of study that encompasses mathematics, computer science, physics, and engineering. An important issue in the study of complex networks is to understand the collective behavior of the elements of these networks. Although the results from graph theory have proven to be powerful in investigating the structures of complex networks, there are few books on the algorithmic aspects of complex network analysis. Filling this need, this book supplies the basic theoretical algorithmic and graph theoretic knowledge needed by every researcher of complex network